2022
DOI: 10.1039/d1en00881a
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose enhances the dispersion and toxicity of ZnO NPs to green algae Eremosphaera viridis

Abstract: The widespread cellulose nanomaterials from industrial production and natural plant degradation inevitably lead to the accumulation of nanocellulose in aquatic environment. However, the effect of nanocellulose on the fate, transport...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…21 The authors explained this by the higher Zn-ion accumulation in the fish when nCu was present. Collectively, the current studies indicated that the potentiation of the effects of multiple ENPs was mainly correlated with increased bioaccumulation of toxic components 22,23 and oxidative stress. 23,24 Conversely, an attenuated toxic effect was found by Zhao et al, 25 who reported that nAl 2 O 3 was shown to mitigate the growth inhibition toxicity of GO to C. pyrenoidosa.…”
Section: Additive Effectsmentioning
confidence: 68%
See 3 more Smart Citations
“…21 The authors explained this by the higher Zn-ion accumulation in the fish when nCu was present. Collectively, the current studies indicated that the potentiation of the effects of multiple ENPs was mainly correlated with increased bioaccumulation of toxic components 22,23 and oxidative stress. 23,24 Conversely, an attenuated toxic effect was found by Zhao et al, 25 who reported that nAl 2 O 3 was shown to mitigate the growth inhibition toxicity of GO to C. pyrenoidosa.…”
Section: Additive Effectsmentioning
confidence: 68%
“…Collectively, the current studies indicated that the potentiation of the effects of multiple ENPs was mainly correlated with increased bioaccumulation of toxic components 22,23 and oxidative stress. 23,24 Conversely, an attenuated toxic effect was found by Zhao et al, 25 who reported that nAl 2 O 3 was shown to mitigate the growth inhibition toxicity of GO to C. pyrenoidosa. Zhao et al 25 explained the reduced exposure of alga to GO in the presence of nAl 2 O 3 due to GO-nAl 2 O 3 heteroaggregation.…”
Section: Additive Effectsmentioning
confidence: 68%
See 2 more Smart Citations
“…ZnO was used to remove various elements and organic pollutants from the environment, and also was used in sunscreens and lotions. [15][16][17][18] The manufacture of plastics, glass, ceramics, pigments, etc. is also inseparable from ZnO nanoparticles (nZnO).…”
Section: Introductionmentioning
confidence: 99%